Two-Loop Control of Redundant Manipulators: Analysis and Experiments on a 3-DOF Planar Arm. (31st January 2013) - Soto, Israel; Campa, Ricardo
A redundant robot has more degrees of freedom (DOF) than those required to accomplish a given motion task. This fact allows the possibility of achieving an additional task, such as avoidance of joint limits or singularities, besides the primary one. Different criteria have been proposed in the literature for the selection of such a secondary task. This paper first recalls some of those criteria and then proposes a two-loop scheme for the motion control of redundant robots. In order to validate the proposed scheme, some experiments are carried out in a direct-drive redundant planar arm which has been designed and built in our laboratory.